(untitled) (Novos Olhares, 2007)
This text addresses the contemporary cinema associated with digital technology and the body. Experience, image and subjectivity are discursive categories highlighted here. In this case, as an example, we take the film "eXistenZ" (1999) by David Cronenberg. Thus, contemporary studies strategically contextualize a theoretical-methodological approach to highlight notions of innovation.